The Development of the Concept of Defect in Accordance with the United Nations Convention on Contracts for the International Sale of Goods for the Year 1980 - Shaheed, Hind; Abdul-Saheb, Ali (Journal of Legal Sciences, 2023)
The Vienna Convention 1980 developed the concept of a defect that necessitates the warranty in a way that is compatible with the requirements of international trade, as it attached it to the obligation of conformity. The agreement also developed the penalties resulting from the existence of the defect, as it imposed on the seller that he is obligated to ensure that his goods conform to the provisions of the contract, as well as that they must be usable. For the purposes for which the goods are used, if the goods are not in conformity, then the seller is in breach of his obligation to conform, as he has delivered defective goods.